Executive Committee Minutes 2016-04-21 - Academic Senate:::::::::
Agenda – item added: Faculty Availability for Student Advising and Office Hours Policy – Approved. Minutes of 4/7/16 – Approved. Chair Report. International Education and Globalization Advisory Committee proposal referred to S&F. Representation on Administrative Appointment Committees policy. Faculty Consultation in Budgetary Matters policy – approved for Senate agenda. Provost Report. Statewide Senator Report. Faculty Availability for Office Hours Policy approved for the Senate agenda. Vice President of Administration & Finance Report. Vice Chair Report. Vice President of Student Affairs Report. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Senate agenda approved. Summer quorum approved.